The Influence of Organizational Culture, Organizational Commitment and Job Satisfaction on Asn Employee Performance : JEL Classification: K11, K12, K13, O34, D23 - Akmal, Akmal; Hamid, Muliyadi; Mujahid, Mujahid (Journal La Bisecoman, 2025)
The purpose of the research This is to analyze influence culture organization to performance employee to performance employee on Office Institution Community Class I Makassar, to analyze influence commitment organization to performance employee to performance employee on Office Institution Community Class I Makassar, to analyze the influence of job satisfaction on employee performance on Office of the Institute Community Class I Makassar and to Analyze influence culture organization, commitment organization And satisfaction Work to performance employee in a way simultaneous or combination. This research is survey research with a quantitative research approach. The location of this research is in the Class I Makassar Correctional Institution (Lapas). The population in this study was 141 people with a sample of 58 people. The main instrument used to obtain data was using a questionnaire. As for the data analysis technique using Multiple Regression analysis technique. Based on the results of this study, it shows that Organizational Culture has a positive and insignificant effect on the performance of civil servants of the Makassar Class I Penitentiary. This means that Organizational Culture has a unidirectional relationship and is not one of the determining factors for the rise and fall of employee performance. Organizational Commitment does not have a positive and insignificant effect on the performance of civil servants of the Makassar Class I Penitentiary. This means that Organizational Commitment has a non-unidirectional relationship and is not one of the determining factors for the rise and fall of employee performance.